Project Managers as Leaders of Innovation in the Telecommunications Industry - Naqi, Abdulla (2010)
The purpose of this research is to measure innovation in the telecom industry in United Arab Emirates (UAE) as it became an important issue especially after liberalizing the telecom sector for competition. The population of this research is directors and project managers who are working in project management office (PMO) in Etisalat organization. The population consists of thirty eight members (five directors and thirty three project managers) .Three main objectives were developed at the beginning of this study. The first objective is to investigate the innovation process , barriers , drivers and the culture that stimulate innovation. Secondly, to investigate the characteristics of the innovative people in the organizations in general and specially the project managers. Thirdly, identify the variables that influence the championing behavior of the project managers. The findings show that innovation is new in UAE specially in the telecom organizations. Therefore, it is recommended to explore more and train employees about this concept. The study revealed that several project managers in the Etisalat didn’t address the vital issues related to the telecom industry by contributing new innovations for developing telecom business solutions in the future. As strong leaders, PM should appreciate the contributions of the employees, give them the authority for decision-making, and prove the higher management that those team members have the competent leadership skills. In addition , project managers have the responsibility of organizing, planning and managing company resources to achieve completion of organizational project objectives and goals. Further, the data results analysis show that there are high positive relationship between different variables such as (championing behavior with level of innovation and problem solving styles and ( decision making authority with influence tactics and problem solving style .)